2019
DOI: 10.1093/bioinformatics/btz076
|View full text |Cite
|
Sign up to set email alerts
|

Gag-protease coevolution shapes the outcome of lopinavir-inclusive treatment regimens in chronically infected HIV-1 subtype C patients

Abstract: Motivation Commonly, protease inhibitor failure is characterized by the development of multiple protease resistance mutations (PRMs). While the impact of PRMs on therapy failure are understood, the introduction of Gag mutations with protease remains largely unclear. Results Here, we utilized phylogenetic analyses and Bayesian network learning as tools to understand Gag-protease coevolution and elucidate the pathways leading t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Barber et al [36] have suggested that PI resistance mutations are more likely to accumulate under prolonged virological failure. Second, there is increasing evidence that mutations in the gag gene play a role in decreasing susceptibility to protease inhibitors by, e.g., inhibiting the proteolytic cleavages necessary for protein maturation [23,59,60]. Virions with immature particles may not adequately complete cell entry or reverse transcription [60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barber et al [36] have suggested that PI resistance mutations are more likely to accumulate under prolonged virological failure. Second, there is increasing evidence that mutations in the gag gene play a role in decreasing susceptibility to protease inhibitors by, e.g., inhibiting the proteolytic cleavages necessary for protein maturation [23,59,60]. Virions with immature particles may not adequately complete cell entry or reverse transcription [60].…”
Section: Discussionmentioning
confidence: 99%
“…To leverage information from large cohorts and cross-sectional studies, different statistical models have been proposed to investigate inter-dependencies of mutations. On the one hand, approaches such as Bayesian networks [21][22][23] and Cox proportionalhazards models [24] provide insights into statistical dependencies between resistance mutations without explicitly modeling the ordering among such mutations. On the other hand, order-aware approaches for investigating evolutionary pathways leading to drug resistance include mutagenetic trees [25,26]; discrete and continuous-time Conjunctive Bayesian Networks (CBN) [27,28]; and Suppes-Bayes Causal Networks (e.g., CAPRI [29,30]).…”
Section: Introductionmentioning
confidence: 99%
“…Barber et al [33] have suggested that PI resistance mutations are more likely to accumulate under prolonged virological failure. Second, there is increasing evidence that mutations in the gag gene play a role in decreasing susceptibility to protease inhibitors by, e.g., inhibiting the proteolytic cleavages necessary for protein maturation [19,55,56]. Virions with immature particles may not adequately complete cell entry or reverse transcription [56].…”
Section: Discussionmentioning
confidence: 99%
“…To leverage information from large cohorts and cross-sectional studies, different statistical models have been proposed to investigate mutational pathways leading to drug resistance. These approaches include several probabilistic graphical models, such as Markov processes [13]; a Markov model incorporating information from phylogenetic trees [4]; mutagenetic trees [3,14]; Bayesian networks [15][16][17][18][19]; discrete and continuous-time Conjunctive Bayesian Networks (CBN) [20,21]; and Suppes-Bayes Causal Networks (SBCN) [22]; as well as a Cox proportional-hazards model which is used to identify pairs of resistance mutations, in which one mutation alters the hazard of the other one [6].…”
Section: Introductionmentioning
confidence: 99%
“…This retrospective study used 24 stored plasma samples obtained from virologically failing PI-treated patients enrolled in the Protease Cleavage Site (PCS) study (2009)(2010)(2011)(2012)(2013) at McCord and King Edward VIII hospitals Durban, South Africa [26]. All enrolled patients received Lopinavir/Ritonavir therapy for at least six months and had plasma HIV-1 RNA levels > 1000 copies/mL.…”
Section: Study Cohortmentioning
confidence: 99%